Bojkot Igrzysk Olimpijskich w Moskwie i Los Angeles w świetle tygodnika „Sportowiec" - Gmur, Marlena (Acta Universitatis Lodziensis. Folia Historica, 2010)
The main aim of this article is to show the reaction of “Sportowiec”, a weekly sports magazine of national range, to the Olympic Games in Moscow and Los Angeles and to what was happening in their background. The core of the article is built on the basis of the arguments used in the magazine, firstly against the boycott of the Olympics declared by the western countries, and secondly those urging the socialist countries to withdraw form the Games in 1984. The part of the article describing the boycott of the Moscow Olympics in 1940 includes an analysis of the information given by “Sportowiec” on the preparations of the games, presentation of politicians’ views, opinions of the sportsmen and people of the cultural world explicitly against the boycott of the Games in Moscow and in support of the authorities; the article also includes an analysis of the information given by “Sportowiec” on the welcoming of the sportsmen, and then assessment of the Polish sportsmen’s performance in the Games. The following fragment of the articles is about the boycott of the Games in the USA declared by the socialist countries, it describes the events from the sportsmen’s point of view. It also includes a commentary on the decision of the USRR National Olympic Committee about withdrawing sportsmens from the Games, and on the Soviet reasoning (which includes the Polish reasoning, too). It is also supposed to present the method in which the magazine described on the one hand the Frienship Competition and on the other about the Olympic Games in Los Angeles. The issues of “Sportowiec” from 1980 and 1984 have been analyzed for this article.